2005
DOI: 10.1136/bmj.38330.470486.8f
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotic drugs and risk of ischaemic stroke: population based retrospective cohort study

Abstract: Objective To compare the incidence of admissions to hospital for stroke among older adults with dementia receiving atypical or typical antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
174
0
9

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(188 citation statements)
references
References 27 publications
5
174
0
9
Order By: Relevance
“…In 2004 the NMA warned against prescription of risperidone and olanzepine for elderly patients with dementia as published data showed a three-fold increase in cerebrovascular incidents in patients prescribed risperidone and olanzepine (Schneider et al, 2005;Brodaty et al, 2003). Later, a similar increased risk of cerebrovascular incidence has been demonstrated in typical antipsychotics as in atypical antipsychotics (Gill et al, 2005;Gill et al, 2007).…”
Section: Discontinuation Of Antipsychotic Medication and Npsmentioning
confidence: 73%
See 1 more Smart Citation
“…In 2004 the NMA warned against prescription of risperidone and olanzepine for elderly patients with dementia as published data showed a three-fold increase in cerebrovascular incidents in patients prescribed risperidone and olanzepine (Schneider et al, 2005;Brodaty et al, 2003). Later, a similar increased risk of cerebrovascular incidence has been demonstrated in typical antipsychotics as in atypical antipsychotics (Gill et al, 2005;Gill et al, 2007).…”
Section: Discontinuation Of Antipsychotic Medication and Npsmentioning
confidence: 73%
“…Newer atypical antipsychotics are believed to have fewer EPS than old typical antipsychotics, but atypical antipsychotics have been found to increase the risk of death and cerebrovascular disease in patients with dementia (Schneider et al, 2005;Ballard et al, 2011a). Cohort studies published thereafter indicated that typical antipsychotics might have even higher mortality rates than atypical antipsychotics (O'Brien, 2008;Gill et al, 2005;Gill et al, 2007). There are some indications of an association between agitation, aggression and psychosis in patients with dementia, which may have encouraged the use of antipsychotic medication for other NPS than psychosis in dementia (Rapoport et al, 2001).…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…It is thus possible that some of the actual events could have been characterized as non-'cerebrovascular' in origin, although this does not mitigate concern about their seriousness. (c) Typical vs atypical antipsychotics: Gill et al (2005) in a retrospective cohort study reported that, after adjustment for potential confounders, participants receiving atypical antipsychotics showed no significant increase in the risk of ischemic stroke compared with those receiving typical antipsychotics (adjusted hazard ratio 1.0, 95% CI 0.8, 1.3). This finding was consistent in subgroup analyses of individual atypical antipsychotic drugs (risperidone, olanzapine, and quetiapine) and selected subpopulations of the total sample.…”
Section: Cerebrovascular Adverse Eventsmentioning
confidence: 99%
“…The lack of placebo-controlled data with specific older conven-tional antipsychotics in patients with dementia cannot be interpreted as indicating that they are without similar risks. Three cohort studies have compared the risk of death or stoke in elderly patients (>65 years) treated with conventional antipsychotic versus atypical antipsychotics (Gill et al, 2005;Herrmann et al, 2004;Wang et al, 2005). Two studies found no significant difference in risk of stroke between the two groups (Gill et al, 2005;Herrmann et al, 2004) while the third found that conventional antipsychotics were associated with a significantly higher adjusted risk of death (Wang et al, 2005).…”
Section: Cerebrovascular Eventsmentioning
confidence: 99%